2019
DOI: 10.1186/s13075-019-1956-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct biomarkers for different bones in osteoporosis with rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is known to cause secondary osteoporosis and fragility fractures. This study aimed to identify biomarkers predictive of bone mineral density (BMD) change at three anatomical sites in patients with RA. Methods We conducted a prospective longitudinal study in patients with RA. In 2012, we recruited 379 patients from an RA cohort, 329 of whom underwent evaluation of blood and urine biomarkers together with measurement of BMD in the lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…Patients with RA often have severe osteoporosis [5,6], which may seriously affect knee functions [7]. TKA might be required [8,9], but studies have yet comprehensively reported the effectiveness of TKA in RA patients with severe osteoporosis and genu valgum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with RA often have severe osteoporosis [5,6], which may seriously affect knee functions [7]. TKA might be required [8,9], but studies have yet comprehensively reported the effectiveness of TKA in RA patients with severe osteoporosis and genu valgum.…”
Section: Discussionmentioning
confidence: 99%
“…Severe osteoporosis is not an absolute contraindication of TKA, but perioperative treatment and preparation are very important. The frequency of osteoporosis is high in patients with RA [5,6], and TKA in such patients can be highly di cult [8,9]. First, improper position, inappropriate traction, and rough operating during TKA could induce bone fracture [8,9,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing OP in RA is correlated with the duration and the severity of the disease ( 19 , 44 ) and even RA pre-menopausal women or men are exposed to a greater risk of osteoporosis in comparison with age- and sex-matched healthy controls ( 45 , 46 ). A prospective longitudinal study on 379 patients identified some biomarkers predictive of BMD change in patients with RA ( 47 ). It was found that the annual BMD change at the lumbar spine had a significant association with glucocorticoids use, bisphosphonate or vitamin D use, and homocysteine.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Accordingly, Cheng et al () reported that anti‐CCP positive patients with RA have higher probability of osteoporotic fracture compared to anti‐CCP negative patients with RA. Furthermore, a recently longitudinal cohort study identified distinct effective biomarkers as predictor changes on BMD in different bones in osteoporosis with RA, being ACPA serum levels a significant predictor of BMD changes in the proximal femur (Tomizawa et al, ). Finally, it has been shown that ACPA positive subjects without clinical signs of RA have significantly lower percentages of trabecular bone volume and cortical bone mineral density at the level of the metacarpal heads compared ACPA negative subjects (Kleyer et al, ).…”
Section: Introductionmentioning
confidence: 99%